2012
DOI: 10.3819/ccbr.2012.70002
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological Studies of Learning and Memory in Pigeons

Abstract: The literature on the neural basis of learning and memory is replete with studies using rats and monkey, but hardly any using pigeons. This is odd because so much of what we know about animal behavior comes from studies with pigeons. The unwillingness to use pigeons in neural studies of learning and memory probably stems from two factors, one that the avian brain is seen as radically different from the mammalian brain and as such can contribute little to its understanding, and the other that the behavior of pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 125 publications
0
10
0
Order By: Relevance
“…Generally, hippocampal lesions in avian brain produce behavioral deficits similar to that in mammalian brain, impairing navigation and spatial memory (see Colombo and Broadbent, ; Colombo and Scarf, , for reviews), prompting researchers to suggest that the avian hippocampus is a functional analogue of mammalian hippocampus. The two notable exceptions in which hippocampal lesions in birds appeared to have different results from that in mammals have been the paired‐associates task and the TI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, hippocampal lesions in avian brain produce behavioral deficits similar to that in mammalian brain, impairing navigation and spatial memory (see Colombo and Broadbent, ; Colombo and Scarf, , for reviews), prompting researchers to suggest that the avian hippocampus is a functional analogue of mammalian hippocampus. The two notable exceptions in which hippocampal lesions in birds appeared to have different results from that in mammals have been the paired‐associates task and the TI.…”
Section: Discussionmentioning
confidence: 99%
“…Although the damage to avian hippocampus produces many of the same spatial memory deficits in mammals (reviewed by Colombo and Scarf, ), until now it appeared to be unnecessary for memory tasks requiring integration of separate pieces of information but devoid of explicit spatial components (Hampton and Shettleworth, ; Colombo et al, ; Coppola et al, ). Specifically, hippocampal lesions were reported to produce no measurable deficits in the paired‐associate task, or, until now, the TI task; in contrast, both of these tasks were reported to be hippocampus‐dependent in rodents (Bunsey and Eichenbaum, ; Dusek and Eichenbaum, ).…”
Section: Discussionmentioning
confidence: 99%
“…The reluctance to accept the idea that anything about the primate brain can be learned from the study of the avian brain might have its origins in the old terminology used to describe bird brains, which suggested that these consist entirely of basal ganglia (Colombo and Scarf, 2012 ). This perspective is now outdated (Reiner et al, 2004 , 2005 ; Jarvis et al, 2005 ), as there is considerable evidence that an important proportion of the avian brain consists of pallial areas, many of them homologous to cortical areas in mammals.…”
Section: The Neurobiological Mechanisms Of Object Recognition: What Wmentioning
confidence: 99%
“…Part of the reason for this lack of surprise is precisely the growing literature that has indicated comparable performance between primates and avians. This literature articulates with the modern recognition that the avian brain enjoys more similarities with the mammalian brain than may have previously been understood (Colombo & Scarf, 2012;Shanahan, Bingman, Shimizu, Wild, & Güntürkün, 2013;Shimizu, 2009). In the past, these parallels may have been unforeseen, given the understanding that mammals have been evolving separately from birds for nearly 300 million years.…”
Section: Discussionmentioning
confidence: 85%